Neural Correlates of Vocal Pitch Compensation in Individuals Who Stutter - Sares, Anastasia G.; Deroche, Mickael L. D.; Ohashi, Hiroki; Shiller, Douglas M.; Gracco, Vincent L. (Frontiers in Human Neuroscience, 2020)
Stuttering is a disorder that impacts the smooth flow of speech production and is associated with a deficit in sensorimotor integration. In a previous experiment, individuals who stuttered were able to vocally compensate for pitch shifts in their auditory feedback, but they exhibited more variability in the timing of their corrective responses. In the current study, we focused on the neural correlates of the task using functional MRI. Participants produced a vowel sound in the scanner while hearing their own voice in real time through headphones. On some trials, the audio was shifted up or down in pitch, eliciting a corrective vocal response. Contrasting pitch-shifted vs unshifted trials revealed bilateral superior temporal activation over all participants. However, the groups differed in activation of middle temporal gyrus and superior frontal gyrus (Brodmann area 10), with individuals who stuttered displaying deactivation while controls displayed activation. In addition to the standard univariate general linear modeling approach, we employed a data-driven technique (independent component analysis, or ICA) to separate task activity into functional networks. Among the networks most correlated with the experimental time course, there was a combined auditory-motor network in controls, but the two networks remained separable for individuals who stuttered. The decoupling of these networks may account for temporal variability in pitch compensation reported in our previous work, and supports the idea that neural network coherence is disturbed in the stuttering brain.